Assessing the impact of the military coup on families in Sagaing Region: A case study of house burnings in Myanmar - Thandar Hlaing (Jurnal Sosiologi Dialektika, 2023)
The military coup in Myanmar triggered a notorious uprising and subsequent armed conflict, resulting in military forces killing and imprisoning protesters, as well as setting fire to houses. This study employs a qualitative approach and uses James Scott’s survival mechanism theory to analyze the hardships experienced by families in fire-damaged villages in the Sagaing region. Our findings reveal that military forces carried out targeted attacks and burned down houses, particularly in villages that supported the People’s Defense Forces, leading to significant suffering among the local population. Families who were victims of this arson faced a host of challenges, including the loss of their homes and possessions, leaving them to seek shelter in the forest or makeshift tents, as well as food insecurity and a lack of access to medical care. Furthermore, many became unemployed as farming production costs were unaffordable and their children were unable to attend school. We highlight the urgent need for international humanitarian aid to address the dire situation faced by families whose homes were burned down by the military in Sagaing Region, Myanmar.